O ciberespaço nas páginas do livro infantojuvenil - Cunha, Leo (Literartes, 2012)
By means of analyses about the creative process designed for the creation of the work Perdido no Ciberespaço (2007), with authorship attributed to the director of this study, the present article aims to trace a path by which it may be possible to capture and understand existing dialogues between copies of contemporary children’s literature and new communication technologies, with special focus to the internet and to the reality of cyberculture.